2023
DOI: 10.1002/andp.202300236
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Deflection Angle and Shadow of Black Hole Solutions in Non‐Plasma and Plasma Mediums Under the Effect of Einstein–Gauss–Bonnet Gravity

Abstract: In this paper, the Gibbons and Werner technique is used to calculate the weak deflection angle for the black hole solution under the effects of Einstein–Gauss–Bonnet gravity. The Gauss–Bonnet theorem in the limits of weak field is used to evaluate the Gaussian optical curvature in order to obtain the results. The visual effects of the deflection angle on the impact parameter is also looked at and the smallest radius in the non‐plasma/plasma medium. Moreover, in order to check the consistency of the results con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…The Keeton and Petters method is used to compute the DA for an accelerating charged AdS BH solution. Keeton and Petters developed that technique to calculate the expression [75][76][77] and to make it more feasible with their approach. The limit of weak deflection is defined as an expansion of series with a single mass m variable in the post-post Newtonian (PPN) framework, which is an easy way to deal with gravity theories in weak field limits.…”
Section: Light-deflected Angle Analysis With the Keeton And Petters A...mentioning
confidence: 99%
“…The Keeton and Petters method is used to compute the DA for an accelerating charged AdS BH solution. Keeton and Petters developed that technique to calculate the expression [75][76][77] and to make it more feasible with their approach. The limit of weak deflection is defined as an expansion of series with a single mass m variable in the post-post Newtonian (PPN) framework, which is an easy way to deal with gravity theories in weak field limits.…”
Section: Light-deflected Angle Analysis With the Keeton And Petters A...mentioning
confidence: 99%
“…[36], and the quasinormal modes in the eikonal limit and the radius of the BH shadow were found to be related in [37,38]. Additional important examinations of the BH shadow and DA were performed in [39][40][41]. The shadow cast by a dyon BH, also known as Kerr-Newman-Kasuya spacetime, was studied in [42], where it was concluded that the shadow image is affected by both its rotational momentum and dyon charge.…”
Section: Introductionmentioning
confidence: 99%